The Effect of Static Fluid Pressure Learning with Predict-Observe-Explain (POE)-Oriented Student Worksheets on Science Process Skills - Nengsih, Desti Purnama; Koto, Irwan; Defianti, Aprina; Nirwana, Nirwana; Johan, Henny (Universitas Muhammadiyah Makassar, 2023)
The purpose of this study was to investigate the effect of static fluid pressure learning with Predict, Observe, Explain (POE)-oriented student worksheets on the eighth-grade students' science process skills. This research employed a non-equivalent control group design. A total of 166 students from five classes in class VIII at State Junior High School 03 in Bengkulu City represented the research population. Students in class VIII-1 (control group) and class VIII-2 (experimental group), for a total of 58 students, were selected as subjects using non-probability sampling and the convenience sampling method. By applying non-parametric inferential statistics, particularly the Mann-Whitney U test, the hypothesis was examined. The results confirm that the use of POE-oriented worksheets in learning the concept of pressure in static fluids has a statistically positive effect at the significance level (0.05) with a p-value (0.003) on science process skills, and the effect size (r=0.39) is in the medium category. The availability of worksheets that rely on scaffolding strategies such as POE may enable students in secondary schools to construct their own knowledge during the learning process.The provision of worksheets that employ scaffolding techniques, such as the Predict-Observe-Explain (POE) approach, has the potential to facilitate the development of students' knowledge construction and science process abilities in secondary school settings.